Analisis Pola Asuh Orang Tua Dalam Pembentukan Karakter Bertanggung Jawab Siswa Kelas V SD Gmim 3 Tomohon - Riswani, Riswani; Tumurang, Hetty J.; Sumilat, Margareta O. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was carried out at SD GMIM 3 Tomohon, aiming to describe parental parenting patterns in forming the responsible character of students at SD GMIM 3 Tomohon. The research method used is qualitative research. The type of research used by researchers in this research is a case study. The data collection techniques for this research are observation, direct interviews, and documentation. The research instruments were the principal, class teachers, students and parents. The data analysis technique uses the Miles and Huberman Model which consists of four stages, namely data collection, data reduction, data presentation and drawing conclusions. Data validity tests in qualitative research include credibility tests (internal validation), transferability (external validation), dependability (reliability), confirmability (objectivity). Ways to test the credibility of data or trust in data resulting from qualitative research include: extending observations, increasing persistence in research, triangulation (tringulation of sources and triangulation of data collection techniques and triangulation of time), analysis of negative cases, using reference materials, conducting check-ups. The conclusion obtained from this research is that the formation of children's character is influenced by the form of parenting patterns of parents at home. This is because parents are the ones who look after and guide children from birth to adulthood. The family is the first and foremost educator.